Chirality induction and chiron approaches to enantioselective total synthesis of alpha-lipoic acid - Chavan, Subhash P.; Pawar, Kailash P.; Praveen, Ch; Patil, Niteen B. (Tetrahedron, 2015)
An efficient, short and convenient asymmetric synthesis of (R)-(+)-lipoic acid in seven steps from chiral hydroxy aldehyde with 32.5% overall yield is described. Synthesis of S and R enantiomers of a-lipoic acid from cis-1,4-butene diol derived chiral lactone is reported with 34 % overall yield. The present synthesis involves use of simple reaction conditions making it a convenient synthesis. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Chiral pool; Chirality induction; enantioselective; Lipoic acid; sharpless asymmetric dihydroxylation

Total synthesis of (R)-lipoic acid and (S)-lipoic acid via an Mn (III)-salen-catalyzed oxidative kinetic resolution - Purude, Abhijeet N.; Pawar, Kailash P.; Patil, Niteen B.; Kalkote, Uttam R.; Chavan, Subhash P. (Tetrahedron-Asymmetry, 2015)
The asymmetric synthesis of both the antipodes of alpha-lipoic acid is described. The total synthesis of racemic and asymmetric lipoic acid is achieved from propane 1,3-diol. This work reports the use of Mn (III)-salen-catalyzed oxidative kinetic resolution as the key step to obtain enantiomerically pure (R)- and (S)-lipoic acid. The undesired product formed during the resolution can be recycled to achieve the desired isomer. (C) 2015 Elsevier Ltd. All rights reserved.

Scalable synthesis of 3-Ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one: an important building block of the antidiabetic drug glimepiride - Chavan, Subhash P.; Pawar, Ambaji A.; Patil, Niteen B.; Kadam, Appasaheb L.; Shinde, Shrikrishna S. (Synthesis-Stuttgart, 2020)
A four-step, practical, and easily scalable synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one, an important building block of the antidiabetic drug glimepiride, has been accomplished. Key features are the synthesis of 3-methyl-4-hydroxy-2-butenolide in water and triflic acid mediated N-benzyl lactam N-deprotection. The main advantages of this process are the scalable synthetic route and decreased number of reaction steps, which paves the way for the industrial-scale synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one.
Keywords: antidiabetic drug; Butenolide; glimepiride; lactams; scalable synthesis

Application of allylic amine formation from aziridine-2-ol under appel reaction condition: synthesis of N-(tert-butoxycarbonyl)-D-vinyl glycine methyl ester - Chavan, Subhash P.; Kawale, Sanket A.; Patil, Niteen B.; Kalbhor, Dinesh B. (Tetrahedron Letters, 2021)
PPh3/I-2/imidazolde mediated allyl amine formation from aziridine-2-alcohol was explored for the synthesis of N-(tert-butoxycarbonyl)-D-vinyl glycine methyl ester. (C) 2021 Published by Elsevier Ltd.
Keywords: Allyl amine; Aziridine-2-alcohol; Aziridinium ion; Birch reaction; Ring opening

Multi-step synthesis of miltefosine: integration of flow chemistry with continuous mechanochemistry - Patil, Niteen B.; Atapalkar, Ranjit S.; Chavan, Subhash P.; Kulkarni, Amol A. (Chemistry-A European Journal, 2021)
Herein we report for the first time, an advanced continuous flow synthesis of the blockbuster Leishmaniasis drug miltefosine from simple starting materials by a sequence involving four steps of chemical transformation including a continuous mechanochemical step. First three reaction steps were performed in simple tubular reactors in a telescopic mode, while in the last step the product precipitated from the 3(rd) step was used for a continuous mechanochemical synthesis of miltefosine. When compared to a typical batch protocol that takes 15 h, miltefosine was obtained in 58 % overall yield in flow synthesis mode at the laboratory scale in a total residence time 34 min at synthesis rate of 10 g/hr, which is sufficient to treat 4800 patients per day.
Keywords: continuous flow; continuous mechanochemistry; miltefosine; multistep synthesis; reactive intermediates